2018
DOI: 10.3892/ijmm.2018.3666
|View full text |Cite
|
Sign up to set email alerts
|

CTRP9 ameliorates cellular senescence via PGC‑1α/AMPK signaling in mesenchymal stem cells

Abstract: Stroke is the second most common cause of death worldwide, and thus, it imposes great financial burdens on both individuals and society. Mesenchymal stem cell (MSC) therapy is a promising approach for ischemic brain injury. However, MSC treatment potential is progressively reduced with age, limiting their therapeutic efficacy for brain repair post‑stroke. C1q and tumor necrosis factor‑related protein 9 (CTRP9) is a novel cytoprotective cytokine with antioxidant effects, which is highly expressed in brain tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In another study, the supplementation of MSCs with nicotinamide (a precursor of NAD + that has been shown to reduce ROS generation) noticeably extended their replicative life span with a significant postponement in the onset of senescence [143]. Recent studies treating animal MSCs with ascorbic acid, or with an antioxidant cytokine C1q and tumor necrosis factor related protein 9 (CTRP9) [144], have also shown promise and need to be tested on human MSCs. In terms of selecting MSC tissue source for expansion, apart from tissue's propensity for certain lineage differentiation or trophic factor secretion, greater consideration should be given to MSC oxidative stress resistance [145] and desirably, longer onset of senescence.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…In another study, the supplementation of MSCs with nicotinamide (a precursor of NAD + that has been shown to reduce ROS generation) noticeably extended their replicative life span with a significant postponement in the onset of senescence [143]. Recent studies treating animal MSCs with ascorbic acid, or with an antioxidant cytokine C1q and tumor necrosis factor related protein 9 (CTRP9) [144], have also shown promise and need to be tested on human MSCs. In terms of selecting MSC tissue source for expansion, apart from tissue's propensity for certain lineage differentiation or trophic factor secretion, greater consideration should be given to MSC oxidative stress resistance [145] and desirably, longer onset of senescence.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…Two recent studies suggest that the anti-apoptotic effects of AdipoR1 agonists are mediated via the phosphatidylinositol 3-kinase (PI3 K)/ protein kinase B (Akt) signaling pathway 19,20 . It has been shown that CTRP9 exerts a high affinity to AdipoR1 21 , and emerging evidence suggests that CTRP9 has the potential to carry out neuroprotective functions on diverse CNS disease 22 . However, the anti-apoptotic effects of CTRP9 following ICH have not yet been illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mouse CTRP9 and human CTRP9 share 84% amino acid identity as well. CTRP9 mainly expresses in adipose tissue, adipocytes and adipose stromal cells and is detectable in variety of tissues and organs, such as skeletal muscle, brain, liver, and kidney (Li, Zhu et al, ; Yang et al, ). It is noteworthy that only human and primates (chimpanzee and rhesus macaque) possess the CTRP9B so far, even though at extremely low expression levels (Peterson et al, ).…”
Section: Introductionmentioning
confidence: 99%